2021
DOI: 10.1002/ccr3.3945
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fat necrosis of the newborn – An atypical case with typical complications

Abstract: Subcutaneous fat necrosis of the newborn should be considered in newborns with suggestive skin lesions, even in the absence of perinatal distress. SCFN may cause long‐standing complications, like hypertriglyceridemia or hypercalcemia. Hypercalcemia can be refractory to therapy and lead to poor weight gain and nephrocalcinosis, which should be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…In both of our patients with nephrocalcinosis, calcium did not normalize until after 2 years of age, suggesting that persistence of hypercalcemia may be an important risk factor for this complication. Long‐term hypercalcemia has been reported in the literature as a complication of SCFN 2,18 . Reassuringly, in both patients, nephrocalcinosis resolved upon serial imaging, in keeping with previous reports.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In both of our patients with nephrocalcinosis, calcium did not normalize until after 2 years of age, suggesting that persistence of hypercalcemia may be an important risk factor for this complication. Long‐term hypercalcemia has been reported in the literature as a complication of SCFN 2,18 . Reassuringly, in both patients, nephrocalcinosis resolved upon serial imaging, in keeping with previous reports.…”
Section: Discussionsupporting
confidence: 88%
“…Long-term hypercalcemia has been reported in the literature as a complication of SCFN. 2,18 Reassuringly, in both patients, nephrocalcinosis resolved upon serial imaging, in keeping with previous reports. Chrysaidou et al reviewed 30 reported cases of SCFN complicated by nephrocalcinosis and nephrolithiasis.…”
Section: T a B L E 1 Demographics And Characteristicssupporting
confidence: 88%
See 2 more Smart Citations